2022
DOI: 10.1111/jpi.12830
|View full text |Cite
|
Sign up to set email alerts
|

Dose assessment of melatonin in sepsis (DAMSEL2) study: Pharmacokinetics of two doses of oral melatonin in patients with sepsis

Abstract: Sepsis is defined as a dysregulated host response to infection, and high-dose melatonin has been proposed as a treatment due to its antioxidant and antiinflammatory properties. However, there are no data describing the pharmacokinetics of high-dose oral melatonin in critically ill patients. We undertook an open-label trial to determine the tolerance of melatonin administration in these patients and pharmacokinetic analysis, to inform a planned randomised controlled trial. Two cohorts of critically ill patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 37 publications
(106 reference statements)
0
5
0
Order By: Relevance
“…Melatonin given in capsules is very rapidly cleared from the circulation. 29 Circadin™ is a prolonged-release formulation of melatonin designed to mimic endogenous secretion, and we used the dose licensed for treating primary insomnia (2 mg). We have showed previously that larger doses of Circadin™ result in prolonged elevation of melatonin concentration which may impact on daytime activities.…”
Section: Discussionmentioning
confidence: 99%
“…Melatonin given in capsules is very rapidly cleared from the circulation. 29 Circadin™ is a prolonged-release formulation of melatonin designed to mimic endogenous secretion, and we used the dose licensed for treating primary insomnia (2 mg). We have showed previously that larger doses of Circadin™ result in prolonged elevation of melatonin concentration which may impact on daytime activities.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical observation led to the conclusion that therapy with melatonin did not lead to any adverse event and was well tolerated. Twenty mg daily was found to be the optimal dose from a pharmacological point of view [ 117 ].…”
Section: Role Of Melatonin In Sepsis and In Sepsis-associated Encepha...mentioning
confidence: 99%
“…However, it has been our report in the 1980s that first demonstrated that melatonin may directly modulate the immune response [72]. Today, the immunoregulatory role of melatonin is widely recognized to the extent that the indoleamine or its agonists have been proposed for the treatment of viral, bacterial, and parasitic infections as well as autoimmune disorders [73][74][75]. Most interesting, it has been reported that melatonin may be of therapeutic value in sepsis and in coronavirus disease 2019 (COVID-19) [76][77][78].…”
Section: Indirect Hormonal Effectsmentioning
confidence: 99%